2022
DOI: 10.1186/s12903-022-02472-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the attachment position in molar intrusion with clear aligners: a finite element study

Abstract: Objective To evaluate the biomechanical effects of different attachments’ position for maxillary molar intrusion with clear aligner treatment by finite element analysis. Methods Cone-beam computed tomography images of a patient with supra-eruption of the maxillary second molars were selected to construct three-dimensional models of the maxilla, periodontal ligaments, dentition, and clear aligner. The models were divided into four groups depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Several studies have highlighted the importance of attachment in enhancing tooth movement [25,27]. The attachments of both the buccal and palatal surfaces of the maxillary posterior teeth can increase the retention of the aligner and help move the teeth more accurately in the horizontal direction [30]. The significant effect of the number of attachments in the maxillary teeth may be due to the disadvantage of retention according to the positional characteristics of the aligners in the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the importance of attachment in enhancing tooth movement [25,27]. The attachments of both the buccal and palatal surfaces of the maxillary posterior teeth can increase the retention of the aligner and help move the teeth more accurately in the horizontal direction [30]. The significant effect of the number of attachments in the maxillary teeth may be due to the disadvantage of retention according to the positional characteristics of the aligners in the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 70–80% of patients may require additional aligners to improve efficiency [ 27 ]. The type and position of attachments are also essential for intrusion achievement [ 28 ], but mesial and distal movement, as one of major tooth movements in alignment, was ignored. Distalization with aligners can be achieved with the sequential movement of the posterior teeth, which means the main movement occurs on the specific tooth in every alignment stage [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four commercially available clear aligners with different material properties include Leon (St. Louis Park, MN, USA), Duran (Scheu-Dental, GmbH, Iserlohn, Germany), Duran Plus (Scheu Dental GmbH, Iserlohn, Germany), and Essix Plus (Dentsply Sirona Deutschland, GmbH, Bensheim, Germany) were designed with thicknesses of 0.8 mm, 1 mm, 0.75 mm, and 0.9 mm, respectively, according to their mechanical characteristics (Table 2 ), [ 27 , 28 ]. A Poisson’s ratio of 0.36 was established for the aligners based on previous studies [ 29 , 30 ]. They were considered isotropic and homogeneous materials [ 26 ].…”
Section: Methodsmentioning
confidence: 99%